5q21 deletion is often heterogeneous in prostate cancer. Issue 8 (24th January 2019) - Kluth, Martina; Al Kilani, Zaid; Özden, Cansu; Hussein, Khakan; Frogh, Sohall; Möller‐Koop, Christina; Burandt, Eike; Steurer, Stefan; Büscheck, Franziska; Jacobsen, Frank; Luebke, Andreas M.; Minner, Sarah; et al.
Abstract: Cancer heterogeneity represents a challenge for the analysis of prognostic molecular markers but can be used to study the evolution of molecular events in tumors. To assess the degree of heterogeneity of 5q21 deletions and their relationship with TMPRSS2 : ERG status and 6q15 deletions in prostate cancer, a heterogeneity tissue microarray including 10 tissue spots from 10 different areas of 317 cancers was analyzed by fluorescence in situ hybridization for 5q21 deletion. Data on 6q and ERG were available from earlier studies. Deletions of 5q21 were found in 23% of 265 interpretable cancers and showed marked intratumoral heterogeneity. In the subset of 246 cancers with at least 3 interpretable spots, 23% had a 5q21 deletion. Heterogeneous 5q21 deletions were found in 71% and homogeneous in 29% of these cancers. The likelihood of 5q21 deletion was twice as high in ERG‐negative (28%) than in ERG‐positive cancers (16%, P = .024). In all 21 cases harboring both alterations, the tumor area containing a 5q21 deletion was smaller or equally large than the ERG‐positive area but never larger. Deletions of 5q and 6q were significantly linked. However, the analysis of 32 tumors harboring both deletions did not suggest a specific order of appearance of these deletions. The 5q21 deletion preceded 6q15 in 10 tumors and 6q15 preceded 5q21 in 14 tumors. In summary, our study identifies 5q21 deletion as a highly heterogeneous aberration in prostate cancer that usually occurs late during cancer progression. This is a severe limitation for using 5q21 testing as a prognostic tool.